An employee satisfaction management framework for the textile and garment industry in Lesotho - Letele, Moeketsi Joseph (University of the Free State, 2018)
Organisations that provide employees with environments that enable unleashing one’s potential enhance employee satisfaction and are regarded as a key source for competitive advantage. However, only little attention is given to the development and implementation of satisfaction management practices that may be linked to improved employee satisfaction. Researchers have found that no organisation can perform optimally unless its employees are satisfied and committed to the success of the organisation. Sustainability of the textile and garment industry in the development of economies depends on the attributes of investors and the effectiveness of government policies or industrial practices. Hence, this study focused on the development of a framework for managing employee satisfaction to enhance employee satisfaction in the textile and garment industry in Lesotho. The literature review discusses factors that affect employee satisfaction and conceptualises employee satisfaction in terms of its relationship with organisational performance. The empirical investigation sought to determine the overall level of employee satisfaction/dissatisfaction, assess contextual determinants of employee satisfaction, and develop an implementation procedure for the strategies that could be incorporated in the framework for managing employee satisfaction to enhance employee satisfaction in the textile and garment industry in Lesotho. In line with a pragmatic paradigm, a convergent mixed-methods design was adopted. To gather quantitative data, a questionnaire was administered. The questionnaire included three sections that comprised a demographic component, the Minnesota Satisfaction Questionnaire (MSQ), and a set of closed-ended questions followed by one open-ended question. This questionnaire was utilised to determine the level of employee satisfaction, factors affecting employee satisfaction, and strategies to improve employee satisfaction in the industry. To gather qualitative data, interviews were conducted. These interviews evinced challenges that contributed to lower employee satisfaction in the textile and garment organisations of Lesotho and strategies for managing employee satisfaction. Data were organised, presented, and analysed by the help of the Statistical Packages for Social Sciences (SPSS) and ATLAS.ti computer packages. On the one hand, quantitative analyses included frequency distributions, bivariate correlations, analyses of variance (ANOVAs) and T-tests. On the other hand, the qualitative analysis utilised content analysis. The analyses of quantitative and qualitative data were done independently, after which the results were triangulated for deeper interpretation. The study established a positive relationship between employee satisfaction and organisational performance. Overall, employee satisfaction was regarded as an antecedent for organisational performance or success. The findings of the study also indicated that employees were moderately dissatisfied with their jobs and organisations in the textile and garment industry in Lesotho. Factors of employee satisfaction and strategies for managing satisfaction were established across three levels, namely the individual, organisational, and industrial levels. Subsequently, this study not only expands the theoretical and empirical literature on employee satisfaction, but also adds knowledge of employee satisfaction from a management perspective. In addition, this study expands knowledge on the mixed-methods approach in investigating employee satisfaction. The results could strengthen the role of all stakeholders in organisations and those outside organisations in supporting this industry in Lesotho. Specifically, the findings of the study can give decision and policy makers some insight into improving employee satisfaction in the textile and garment industry in Lesotho. By doing so, the performance of the whole textile and garment industry will likely improve and translate into the national economic upliftment of the country. The findings of the study could also be used as a baseline for similar studies on the textile and garment industries in other countries.
Keywords: Employee satisfaction; Employee motivation; Work adjustment; Employee satisfaction management; Textile and garment industry; Organisational performance; Mixed methods; Industrial relations; Thesis (PhD (Business Administration)) - University of the Free State, 2018